2021
DOI: 10.3390/app11188553
|View full text |Cite
|
Sign up to set email alerts
|

Resective Surgery versus Debridement in Stage 2 Medication-Related Osteonecrosis of the Jaw

Abstract: The aim of this study is to analyze surgical and functional outcomes in order to verify the applicability of surgical treatment guidelines as foreseen by MASCC/ISOO/ASCO 2019. Patients affected by stage 2 MRONJ refractory to conservative management were grouped if underwent surgical resection (Group A) or debridement (Group B). Health-related quality of life was evaluated by using the European Organization for Research and Treatment of Cancer questionnaires, QLQ-C30 and H&N35. Statistical analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Both the American and Italian guidelines advocate for abandoning the principle of avoiding invasiveness to protect patients’ quality of life and instead prioritize achieving healthy and viable bony margins. Careful planning is crucial and can significantly impact the success of the procedure [ 23 , 25 ]. Most surgeons determine “vital bone” based on intraoperative observation of bleeding margins [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both the American and Italian guidelines advocate for abandoning the principle of avoiding invasiveness to protect patients’ quality of life and instead prioritize achieving healthy and viable bony margins. Careful planning is crucial and can significantly impact the success of the procedure [ 23 , 25 ]. Most surgeons determine “vital bone” based on intraoperative observation of bleeding margins [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…The rationale behind this protocol derives from the pharmacokinetics of bisphosphonates and denosumab, the former retains a half-live of 10 to 12 years, while the latter of 25.4 days 36. However no consensus was reached up today as guidelines and position papers published are based on expert opinion rather than prospective studies and a systematic review performed by Campisi and colleagues failed to provide clear evidence on the correct protocol to follow 37–39. A randomized trial performed by Ottesen et al,40 indicate that drug holiday does not prevent development of MRONJ after surgical tooth extraction and leads to general health state decline, when compared with drug continuation and that denosumab drug holiday has no effect on healing outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may represent a challenging goal to achieve, as a significant percentage of treated patients typically do not benefit from the received treatments. Moreover, some ongoing controversies exist regarding how the surgeon should decide between a conservative or aggressive treatment [5]. During the last few years, the research in cell therapy revealed interesting perspectives.…”
Section: Introductionmentioning
confidence: 99%